Systemic delivery of IL‐27 by an adeno‐associated viral vector inhibits T cell‐mediated colitis and induces multiple inhibitory pathways in T cells. Issue 2 (22nd April 2016) - Zhu, Xiaotong; Liu, Zhihao; Liu, Jin‐Qing; Zhu, Jianmin; Zhang, Jianchao; Davis, Jonathan P.; Chu, Jianhong; Yu, Jianhua; Zhou, Jie; Li, Ming‐Song; Bai, Xue‐Feng
Abstract : Administration of AAV‐IL‐27 blocks autoimmune colitis via novel mechanisms. Abstract : IL‐27 is a heterodimeric cytokine that is composed of two subunits, i.e., EBV‐induced gene 3 and IL‐27p28 (also known as IL‐30). Although the role of endogenous IL‐27 in the pathogenesis of autoimmune colitis, an experimental model of human inflammatory bowel disease, remains controversial, IL‐27 local delivery has been shown to inhibit autoimmune colitis. IL‐30 has been shown to inhibit Th1 and Th17 responses and is considered a potential therapeutic for certain autoimmune diseases. In this study, we have compared the therapeutic efficacy of adeno‐associated viral vector‐delivered IL‐27 and IL‐30 in a murine model of autoimmune colitis. We found that 1 single administration of adeno‐associated viral vector‐delivered IL‐27, but not adeno‐associated viral vector‐delivered IL‐30, nearly completely inhibited autoimmune colitis. Adeno‐associated viral vector‐delivered IL‐27 administration inhibited Th17 responses and induced T cell expression of IL‐10, programmed death ligand 1, and stem cell antigen 1. Intriguingly, adeno‐associated viral vector‐delivered IL‐27 treatment enhanced Th1 responses and inhibited regulatory T cell responses. Experiments involving the adoptive transfer of IL‐10‐deficient T cells revealed that adeno‐associated viral vector‐delivered IL‐27‐induced IL‐10 production was insufficient to mediate inhibition of autoimmune colitis, whereas anti‐programmed death 1 antibody treatment resulted in the breaking of adeno‐associated viral vector‐delivered IL‐27‐induced T cell tolerance. Thus, systemic delivery of IL‐27 inhibits Th17 responses and induces multiple inhibitory pathways, including programmed death ligand 1 in T cells, and adeno‐associated viral vector‐delivered IL‐27, but not IL‐30, may have a therapeutic potential for the treatment of human inflammatory bowel disease.